ANALISIS PEMAHAMAN GURU BIMBINGAN KONSELING TERHADAP GENDER DALAM LAYANAN KONSELING BERBASIS SYARIAT ISLAM - Anwar, Faisal; Julia, Putry; Ifanna, Ifanna (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2023)
Abstract: In the province of Aceh, gender equality is still not fully understood by the community, and many face limitations in comprehending the concept. In the implementation of counseling in schools where Islamic law must be adhered to, alongside the demand for guidance and counseling teachers to understand gender equality, it becomes a challenge for them, especially in higher-level schools.The purpose of this research is to gain a deep understanding of how guidance and counseling teachers perceive and face challenges related to gender when providing counseling services under Islamic Sharia Law (Qanun). Additionally, it seeks to uncover the efforts made by these teachers to enhance their own understanding and that of their students regarding gender. This study employed a qualitative descriptive research design with a sample size of four individuals from four different schools, selected purposively through interview techniques. The research findings indicate that guidance and counseling teachers' understanding of gender in school counseling services is influenced by Qanun Islamic Law. There is a variety of perspectives regarding gender differences in Islam, the roles of gender in society, and conservative views on leadership. However, within the school context, gender equality in leadership and students' rights are upheld. In counseling practice, teachers share similar concepts, emphasizing the importance of location and ethical considerations when dealing with adult male students. Challenges include discomfort in addressing the needs of adult male students that require physical contact while adhering to the Islamic prohibition of being alone with unrelated individuals (khalwat). These challenges can be overcome with time. Notably, Qanun Sharia Law does not impose specific limitations on gender in the context of children. Guidance and counseling teachers provide children with the space to resolve their own issues, in accordance with counseling principles in Islam. To improve their understanding of gender based on Qanun Sharia Law, guidance and counseling teachers seek additional information and references that are relevant to the Islamic legal framework.Keywords: Gender; Guidance and Counseling; Qanun Islamic Law.Abstrak: Di Provinsi Aceh, kesetaraan gender masih belum sepenuhnya dipahami oleh masyarakat, dan banyak yang menghadapi keterbatasan dalam memahami konsep tersebut. Dalam penerapan konseling di sekolah dimana syariat Islam harus dijalankan disamping guru BK dituntut untuk memahami kesetaraan gender menjadi tantangan sendiri bagi mereka khususnya di sekolah tingkat atas. tujuan penlitian ini adalah untuk mencari tau secara mendalam seperti apa pemahaman dan kendala para guru bimbingan dan konseling terhadap gender dalam memeri layanan konseling dibawah qanun syariat Islam. Disamping itu juga untuk mencari tau apa saja usaha yang dilakukan oleh para guru bimbingan dan konseling untuk meningkatakan pemahaman mereka dan para siswa mengenai gender. Penelitian ini merupakan penelitian kualitatif deskriptif dengan jumlah partisipan sebanyak 4 orang dari 4 sekolah yang berbeda yang diambil secara purposive sampling, data yang dikumpulkan menggunakan teknik wawancara secara mendalam. Hasil penelitian menunjukkan pemahaman guru Bimbingan dan Konseling tentang gender dalam layanan konseling sekolah berdasarkan Qanun Syariat Islam. Terdapat variasi pemahaman mengenai perbedaan gender dalam Islam, peran gender dalam masyarakat, dan pandangan konservatif tentang pemimpinan. Namun, di sekolah, kesetaraan gender dalam kepemimpinan dan hak-hak siswa dijunjung. Dalam praktik konseling, guru memiliki konsep serupa, memperhatikan lokasi dan etika saat berhadapan dengan siswa laki-laki dewasa. Kendala-kendala termasuk ketidaknyamanan dalam menangani siswa laki-laki dewasa yan memerlukan sentuhan fisik, namun harus mematuhi larangan berkhalwat dalam Islam. Kendala ini dapat diatasi seiring berjalannya waktu. Qanun Syariat Islam tidak memiliki batasan khusus mengenai gender anak-anak, dengan guru memberi anak-anak ruang untuk menyelesaikan masalah mereka sendiri, sesuai prinsip konseling dalam Islam. Untuk meningkatkan pemahaman tentang gender berdasarkan Qanun Syariat Islam, guru Bimbingan dan Konseling mencari informasi tambahan dan referensi sesuai konteks syariat Islam. Kata Kunci: Gender; Bimbingan dan Konseling; Qanun Syariat Islam